FENOMENA VIRAL DI MEDIA SOSIAL DAN DAMPAKNYA TERHADAP PERILAKU SOSIAL - Suci Emelsi Jeffri (Al Amin : Jurnal Kajian Ilmu dan Budaya Islam, 2025)
Viral phenomena on social media have become an important part of the life of modern society that affect communication patterns and social behavior. This study aims to analyze the impact of virality on people's social behavior, especially in the context of consumption and social interaction. The method used is descriptive qualitative with literature studies as data sources. The results of the study show that virality is able to accelerate the dissemination of information as well as affect consumptive patterns and the way individuals build social identity. The positive impact can be seen in economic opportunities, especially for MSME actors who can take advantage of virality to increase market reach. However, virality also poses negative risks such as impulsive consumerism, social pressure, and the spread of inaccurate information due to low digital literacy. Therefore, it is important to increase digital literacy so that the public can respond to viral phenomena critically and responsiblye